A day in the life: psychological impact on emergency responders during the 22 March 2016 terrorist attacks - Muysewinkel, Emilie; Vesentini, Lara; Van Deynse, Helena; Vanclooster, Stephanie; Bilsen, Johan; Van Overmeire, Roel (Frontiers in Psychiatry, 2024)
Introduction: Terrorist attacks can cause severe long-term mental health issues that need treatment. However, in the case of emergency responders, research is often vague on the type of stressors emergency responders' encounter. For example, in addition to the threat they work under, studies have shown that ill-preparation adds to the stress experienced by emergency responders. Yet, few studies have looked into the experience of emergency responders. In this study, we looked at the experience of emergency responders during the 22/03/2016 terrorist attacks in Belgium.Methods: We used a qualitative design, in which we interviewed different types of emergency responders. Police officers, nurses, soldiers, firefighters and Red Cross volunteers were included. Interviews were coded by two researchers and analysed using a thematic approach.Results: Four large themes were developed: constant threat and chaos, frustrations with lack of preparedness and training, ethical decisions and debriefings. While emergency responders encountered constant threat, in addition they often felt that they were ill-prepared for such attacks. One specific example was their lack of training in tourniquet-usage. Furthermore, in a disaster setting, the emergency responders had to make life-and-death decisions for which they were not always prepared. Finally, debriefings were conducted in the aftermath of the attacks. While most were perceived as positive, the debriefings among police officers was viewed as insufficient.Conclusions: Emergency responding to terrorist attacks has many different dimensions of events that can cause stress. Our study revealed that preparation is key, both in terms of material, but also in terms ethics and debriefings.